The Retrospective Raj : Medicine, Literature and History after Empire. - Goodman, Sam. (Edinburgh : Edinburgh University Press, 2022)
Explores the 20th century literary revival of Empire and the post-imperial novel through a critical medical humanities lens.
Frontmatter -- Contents -- Acknowledgements -- Abbreviations -- Introduction: Retrospective Diagnosis: Medicine and Post-Imperial Literature -- Chapter 1 Colonial Conditions: On Being Ill in the Anglo-Indian Novel -- Chapter 2 Surgery for the Novel: Medical Practitioners in Anglo-Indian Fiction -- Chapter 3 Know Your Place: Space, Environment and Medicine -- Chapter 4 Death by the Bottle or the Spoon: Diet, Health and Well-Being -- Chapter 5 No Such Thing as History Nowadays: Medicine, Health and the Legacy of Empire -- Conclusion: Imperial Sunsets -- Bibliography -- Index
Description based upon print version of record.
Includes bibliographical references and index.
JSTOR
Keywords: Medicine in literature; English fiction -- 20th century -- History and criticism; Postcolonialism in literature; Imperialism in literature; Medicine in Literature; Médecine dans la littérature.; Roman anglais -- 20e siècle -- Histoire et critique; Postcolonialisme dans la littérature.; Impérialisme dans la littérature.; LITERARY COLLECTIONS / Asian / General; English fiction; Imperialism in literature; Medicine in literature; Postcolonialism in literature; 1900-1999; Criticism, interpretation, etc